Introducing a nonvolatile N-type dopant drastically improves electron transport in polymer and small-molecule organic transistors - Panidi,J; Kainth,J; Paterson,AF; Wang,S; Tsetseris,L; Emwas,AH; McLachlan,MA; Heeney,M; Anthopoulos,TD (Advanced Functional Materials, 2019)
KGaA, Weinheim Molecular doping is a powerful yet challenging technique for enhancing charge transport in organic semiconductors (OSCs). While there is a wealth of research on p-type dopants, work on their n-type counterparts is comparatively limited. Here, reported is the previously unexplored n-dopant (12a,18a)-5,6,12,12a,13,18,18a,19-octahydro-5,6-dimethyl- 13,18[1′,2′]-benzenobisbenzimidazo [1,2-b:2′,1′-d]benzo[i][2.5]benzodiazo-cine potassium triflate adduct (DMBI-BDZC) and its application in organic thin-film transistors (OTFTs). Two different high electron mobility OSCs, namely, the polymer poly[[N,N′-bis(2-octyldodecyl)-naphthalene-1,4,5,8- bis(dicarboximide)-2,6-diyl]-alt-5,5′-(2′-bithiophene)] and a small-molecule naphthalene diimides fused with 2-(1,3-dithiol-2-ylidene)malononitrile groups (NDI-DTYM2) are used to study the effectiveness of DMBI-BDZC as a n-dopant. N-doping of both semiconductors results in OTFTs with improved electron mobility (up to 1.1 cm2 V−1 s−1), reduced threshold voltage and lower contact resistance. The impact of DMBI-BDZC incorporation is particularly evident in the temperature dependence of the electron transport, where a significant reduction in the activation energy due to trap deactivation is observed. Electron paramagnetic resonance measurements support the n-doping activity of DMBI-BDZC in both semiconductors. This finding is corroborated by density functional theory calculations, which highlights ground-state electron transfer as the main doping mechanism. The work highlights DMBI-BDZC as a promising n-type molecular dopant for OSCs and its application in OTFTs, solar cells, photodetectors, and thermoelectrics.